Impact of Financial Crisis on the Profitability of Capital Structure Arbitrage in Australia (International Journal of Banking and Finance, 2016)
We evaluate the performance of a convergence style capital structure arbitrage trading strategy using Australian CDS spreads estimated by the Credit Grades model. By comparing a number of volatility inputs, we find that although option-implied volatility inputs produce biased spreads compared to historical measures, their correlation with medium-term changes in market spreads generate significantly more profitable trades during the financial crisis, even after the inclusion of transaction costs. While the strategy is risky at both the individual obligor and the iTraxx Index level, combining positions into an equally-weighted index of arbitrage trades reduces risk.